RADIOGRAPHIC EVALUATION OF MAXILLARY 1st PREMOLAR DEVELOPMENT BASED ON NOLLAS STAGE OF TOOTH DEVELOPMENT IN 7- 9 YEAR OLD MALE CHILDREN - A RETROSPECTIVE ANALYSIS - karpagam, G.Nithya; lakshmi T, Bhagya; prabu, Dinesh (International Journal of Psychosocial Rehabilitation, 2025)
The aim of the study is to radiographically evaluate the maxillary first premolar development based on nollas stage of tooth development in 7 to 9 year old male children. A total of about 400 orthopantomography (OPG) images were collected from the database record of the dental institution between June 2019-March 2020. Of these 200 OPGs were selected based on the age group between 7-9 years old male children. Dental age of developing permanent first maxillary premolar was calculated based on the nollas method after data collection statistical analysis was done in SPSS software. Among the study population 68% were 7 years old, 13% were 8 years old and 19% were 9 years old. Considering the distribution of teeth assessed 52.5% were 14 and 47.5% were 24. Majority of the teeth attained maximum development at stage 4(45%), and the least assessed at stage 1(1%). The association between the age and nollas stage of tooth development showed p-value of 0.082(p>0.05) the difference is statistically not significant. And the association between the tooth number and nollas stage of tooth development showed p value-0.054,p(>0.05), which is statistically not significant. Within the limitations of the study it was concluded that, majority of the maxillary first premolar teeth assessed among 7 to 9 years old male children had premolar ‘crown almost completed’ (Stage 4) according to Nollas stage of tooth development. Majority of the children in the age group of 7 and 9 years had 2/3rd crown completed in premolar(Stage 4) and majority of 8 years old children had ‘crown almost completed’ in premolar (Stage 5)